2010
DOI: 10.1007/s10532-010-9439-8
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification of a landfill leachate with high nitrate concentration in an anoxic rotating biological contactor

Abstract: The denitrification performance of a lab-scale anoxic rotating biological contactor (RBC) using landfill leachate with high nitrate concentration was evaluated. Under a carbon to nitrogen ratio (C/N) of 2, the reactor achieved N-NO(3)(-) removal efficiencies above 95% for concentrations up to 100 mg N-NO(3)(-) l(-1). The highest observed denitrification rate was 55 mg N-NO(3)(-) l(-1) h(-1) (15 g N-NO(3)(-) m(-2) d(-1)) at a nitrate concentration of 560 mg N-NO(3)(-) l(-1). Although the reactor has revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Based on the results of research conducted at various discharge ozone and the contact time corresponding factorial design, the percentage of COD removal from leachate at pH 11 was higher than the percentage removed at the original pH (pH 8.3). This was similar to the findings by Cortez et al (2010a) at alkaline pH. They found that more molecules of ozone decomposed to form hydroxyl ions (OH -) and hydroxyl radicals (OH•).…”
Section: Ph Influence In Cod Removalsupporting
confidence: 89%
“…Based on the results of research conducted at various discharge ozone and the contact time corresponding factorial design, the percentage of COD removal from leachate at pH 11 was higher than the percentage removed at the original pH (pH 8.3). This was similar to the findings by Cortez et al (2010a) at alkaline pH. They found that more molecules of ozone decomposed to form hydroxyl ions (OH -) and hydroxyl radicals (OH•).…”
Section: Ph Influence In Cod Removalsupporting
confidence: 89%
“…This behavior corroborates the work by Cortez et al (2010), who treating leachate from landfill in contact reactor found the values between 6.4 and 7.3 for the CL and from 7.8 -9.4 for the TL. This behavior, according to Cortez et al (2011), is due to the consumption of hydrogen ions resulting from the conversion of N-NO 3 to nitrous oxides in the reactor due to denitrification process. However, since no analysis of nitrogen was carried out, it is not possible to allege that this behavior is due to the denitrification process.…”
Section: Resultsmentioning
confidence: 99%
“…Overall removal of dissolved metals ranged from 19% for nickel to 59% for manganese (Henderson and Atwater 1995). The denitrification performance of a laboratory-scale rotating biological contactor using landfill leachate-from a municipal landfill in the North of Portugal-with high nitrate concentration was evaluated by Cortez et al (2011). Under a carbon-to-nitrogen ratio (C/N) of 2, the reactor achieved N-NO 3 -removal efficiencies above 95% for concentrations up to 100 mg N-NO 3 -per 1 L. The effectiveness of COD removal was about 90%.…”
Section: Rotating Biological Contactors and Reverse Osmosismentioning
confidence: 99%